PLZ, WILL PAY ALOT!!!!!!!!!

Algebra
Tutor: None Selected Time limit: 1 Day

Mar 21st, 2015

From the first equation, y = - x - 2. Substitute it into the second equation: x - (- x - 2) = - 8.

x + x + 2 = -8; 2x = -10; x = -5. Finally, y = -(-5) - 2 = 5 - 2 = 3.

Answer: c

Mar 21st, 2015

Are you studying on the go? Check out our FREE app and post questions on the fly!
Download on the
App Store
...
Mar 21st, 2015
...
Mar 21st, 2015
Dec 7th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer